Effects of arsenic and phosphorus on the growth and nutrient concentration in rice plant - Howladar, MM; Uddin, MJ; Islam, MM; Parveen, Z; Rahman, MK (Journal of Biodiversity Conservation and Bioresource Management, 2019)
A pot experiment was carried out with arsenic (As) viz. 0, 0.1, 1 and 2 mgL-1 as sodium arsenite and phosphorus viz, 0, 15 and 30 μgmL-1 as ammonium dihydrogen phosphate to evaluate their effects on dry matter yield and nutrients concentration in rice plants (Oryza sativa L.) in the net house. Arsenic toxicity caused more damage to root than to shoot. As reduced plant height and dry matter yields but lower level increased the same significantly. A maximum diminution of 26.70% shoot weight and 32.30% root weights were observed where 2 mgL-1As and 0 μgmL-1 P were applied. Micronutrients were found to be more strongly antagonized by arsenic than the macronutrients. Maximum and minimum accumulation of different nutrients was found at 30 μgmL-1 and 0 μgmL-1 P applications, respectively. The lowest concentration of most of the nutrients were found at 2 mgL-1As and 0 μgmL-1 P. Experiment revealed that the concentrations of nitrogen, potassium, sulphur, iron, copper, zinc and manganese in the root and shoot of rice plants showed an antagonistic effect with As and synergistic effect with P. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 31-38